Aplicação de sanções positivas no direito do trabalho brasileiro - Rômulo Soares Valentini (2012)
Brazils social and economic situation leads to a scenario in which the breach of labor legislation becomes more advantageous for companies, under the financial aspect, than to act as predicted by the law. The traditional legal theory aims to curb this behavior by improving the efficiency of punitive sanctions in order to repress the illegal conduct, making it unprofitable for those who opt to act in disrespect to the law. This paper intends to shed bases for resolving the issue through another approach, consistent in the creation of legal rules that aim to make law enforcement more advantageous to the agents, establishing positive sanctions. This logic, guided by the promotional function of law, allows the creation of a normative model capable of acting together with the repressive logic to ensure maximum effectiveness of legal standards and promote voluntary compliance of the legislation.